STRATEGI PEMASARAN BALI APOLLO DIVE AND WATER SPORT UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN - Fatahilah Sani, Vicky; Eka Mahadewi, Ni Putu; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
Bali Apollo Dive & Water Sport is a company that provides various types of activities and water sports in Tanjung Benoa. Along with the development of tourism in Bali, the interest of tourists to carry out water sport activities is increasing so that many stakeholders have established a water sport tourism business which makes competition between water sport companies tight, therefore this phenomenon is the background of this research The data collection methods used in this study were observation, interviews, documentation, literature studies and the distribution of internal and external questionnaires to 150 respondents who used the Bali Apollo Dive & Water Sport water sport tour package as well as to the Bali Apollo Dive & Water Sport and academics. Tourism. The results of the study The results of the study using 17 internal environmental sub-indicators and 11 external environmental sub-indicators, then obtained 14 strength factors, 3 weakness factors, 8 opportunity factors and 3 threat factors. Based on the results of data processing on external internal factors/IFAS EFAS Bali Apollo Dive & Water Sport, it is known that the total value of IFAS is 3.17 and the total value of EFAS is 2.31, indicating the position of the Bali Apollo Dive & Water Sport water sport package is in cell VIII, namely Conglomerate Growth and Diversification Strategy. In this position, the strategy used by Bali Apollo Dive & Water Sport in marketing water sport packages requires a growth strategy through strategic emphasis on financial synergies rather than product marketing synergies.